2020
DOI: 10.1002/pon.5583
|View full text |Cite
|
Sign up to set email alerts
|

Threshold score for the self‐report Pediatric Distress Thermometer Rating Scale in childhood cancer patients

Abstract: Objective Although there is enthusiasm for identifying and treating psychosocial problems in childhood cancer patients, there are few validated instruments to help providers identify at‐risk children for further assessment. The study objective was to evaluate the sensitivity and specificity of the self‐report pediatric Distress Thermometer Rating Scale (Peds DTRS) in childhood cancer survivors and identify a threshold score to help providers classify pediatric patients. Methods We evaluated 54 children 7–17 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The Pediatric Distress Thermometer is a one item screening tool that measures distress, defined as worry, anxiety, sadness, or fear, reported by the child on a visual analogue scale from 0 (no distress) to 10 (severe distress), based on the child’s experience in the previous week [ 40 ]. A recent study has identified threshold scores for children with cancer [ 42 ]. The FACES pain scale also uses a visual analogue scale to assess intensity of pain and is validated from age 4 years onwards (and caregiver proxy).…”
Section: Methods and Designmentioning
confidence: 99%
“…The Pediatric Distress Thermometer is a one item screening tool that measures distress, defined as worry, anxiety, sadness, or fear, reported by the child on a visual analogue scale from 0 (no distress) to 10 (severe distress), based on the child’s experience in the previous week [ 40 ]. A recent study has identified threshold scores for children with cancer [ 42 ]. The FACES pain scale also uses a visual analogue scale to assess intensity of pain and is validated from age 4 years onwards (and caregiver proxy).…”
Section: Methods and Designmentioning
confidence: 99%
“…The United States National Comprehensive Cancer Network (NCCN) distress thermometer (DT) was developed according to these needs and it allows for a quick and easy survey of distress (Jacobsen et al 2005 ). Previous studies have shown that its use is reliable, valid and acceptable in pediatric cancer patients (Patel et al 2010 , 2011 , 2014 , 2021 ; Schulte et al 2019 ; Wiener et al 2017 ). With the help of the DT, the child can classify his or her subjectively experienced stress on a visual analog scale with the subdivisions 0 (no stress) to 10 (extreme stress).…”
Section: Introductionmentioning
confidence: 99%
“…Outcome measures included two scales for measuring distress levels and anxiety: the Distress Thermometer [15,16] and the RCMAS-2 [17]. The Pediatric Distress Thermometer consists of a self-reported scale and has been validated as a screening tool for distress in pediatric oncology [16]. A value above 3 has been indicated as reasonable for identifying distress in children [16].…”
mentioning
confidence: 99%
“…The Pediatric Distress Thermometer consists of a self-reported scale and has been validated as a screening tool for distress in pediatric oncology [16]. A value above 3 has been indicated as reasonable for identifying distress in children [16]. The score from the RCMAS-2 scale represents the sum of the results of the whole RCMAS-2 scale and aims to detect a level of general anxiety.…”
mentioning
confidence: 99%